2020
DOI: 10.1002/jclp.22963
|View full text |Cite
|
Sign up to set email alerts
|

Switch, a new intervention that targets motivational negative symptoms in people with schizophrenia: An uncontrolled pilot study

Abstract: Objective People diagnosed with schizophrenia experience difficulties in their daily life, which is best explained by motivational negative symptoms. This study explores the feasibility, acceptability, and efficacy of Switch, a new multifactorial intervention that targets motivational deficits. Method Eight participants with schizophrenia or schizoaffective disorder followed around 30 individual sessions of Switch over 12 months. Participants and their informants were interviewed at baseline (T0), at 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The Switch intervention was created based on a model of motivation and goal directed behaviours and followed the same principles as previously described (Thonon, Levaux, et al, 2020;Thonon, Van Aubel, et al, 2020). Furthermore, different principles of learning were adhered to in order to enhance the potential of the intervention in the group format.…”
Section: Intervention: Switchmentioning
confidence: 99%
See 1 more Smart Citation
“…The Switch intervention was created based on a model of motivation and goal directed behaviours and followed the same principles as previously described (Thonon, Levaux, et al, 2020;Thonon, Van Aubel, et al, 2020). Furthermore, different principles of learning were adhered to in order to enhance the potential of the intervention in the group format.…”
Section: Intervention: Switchmentioning
confidence: 99%
“…Yet, adequate treatment schemes for motivational negative symptoms have been largely lacking. In the past few years, however, new interventions that specifically target motivational deficits have been developed and tested (e.g., Favrod et al, 2019;Thonon, Levaux, Della Libera, & Larøi, 2020). For example, our research group has found promising results from the "Switch" intervention provided in individual sessions, with specific improvements on motivational negative symptoms and functional outcomes (Thonon, Levaux, et al, 2020), as well as particular effects on daily life measures of savouring abilities, cognition (e.g., discouraging beliefs), and the engagement in meaningful and effortful activities (Thonon, Van Aubel, Lafit, Della Libera, & Larøi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [9], we presented a model of motivation in schizophrenia that integrates various emotional/hedonic, (neuro) cognitive and behavioural processes that are related to motivation and goaldirected behaviours and that are often dysfunctional in individuals with schizophrenia. This model was predominantly inspired by the model developed by Kring and Barch, which follows the course of hedonic processes, from the anticipation of a reward to its obtainment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the experience of successfully moving towards one's goal can be Fig. 1 Three-level model of motivation (reproduced with permission from [9]) recalled (reminiscence) and can feed further anticipation (for a more detailed description and an illustration, see [9]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation